2018
DOI: 10.3126/jnarc.v4i1.19688
|View full text |Cite
|
Sign up to set email alerts
|

Soil Fertility Assessment and Mapping of Regional Agricultural Research Station, Parwanipur, Bara, Nepal

Abstract: Soil fertility assessment is a key for sustainable planning of a particular area. Thus, the present study was conducted to assess the soil fertility status of the Regional Agricultural Research Station, Parwanipur, Bara, Nepal. The study area is situated at the latitude 27°4’40.9’’N and longitude 84°56’9.85”E at 75masl altitude. Altogether 76 soil samples were collected based on the variability of land at 0-20 cm depth. The texture, pH, OM, total N, available P2O5, K2O, Ca, Mg, S, B, Fe, Zn, Cu and Mn content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 9 publications
4
16
0
1
Order By: Relevance
“…The distribution of available boron was very low only ( Figure 11). The very deficient status of available boron was also reported by Khadka et al (2016Khadka et al ( , 2017Khadka et al ( , 2018 during their study in the different sites of Nepal. The intense cultivation of crops without application of boron containing fertilizer might be the cause of deficient status of available boron in the field.…”
Section: Available Boronsupporting
confidence: 61%
See 2 more Smart Citations
“…The distribution of available boron was very low only ( Figure 11). The very deficient status of available boron was also reported by Khadka et al (2016Khadka et al ( , 2017Khadka et al ( , 2018 during their study in the different sites of Nepal. The intense cultivation of crops without application of boron containing fertilizer might be the cause of deficient status of available boron in the field.…”
Section: Available Boronsupporting
confidence: 61%
“…The distribution of available sulphur was very low merely ( Figure 11). Khadka et al (2016Khadka et al ( , 2017Khadka et al ( , 2018 also reported very critical status of available sulphur in the different sites of Nepal. The intense cultivation of crops without application of sulphur containing fertilizer might be the cause of deficient status of available sulphur in the field.…”
Section: Available Sulphurmentioning
confidence: 85%
See 1 more Smart Citation
“…The site is located in the central piedmont of Nepal at 120 m above mean sea level at 27°21′N and 84°53′E. The soil is with pH 5.67, i.e., moderately acidic (Bhurer, 2013;Khadka et al, 2018).The soil is an Inceptisol formed on Himalayan residuum. The area has a subtropical climate highly influenced by the southwestern monsoon.…”
Section: Methodsmentioning
confidence: 99%
“…From 1971 to 2014, the average minimum and maximum temperature of 18.4 and 30.5°C with an average annual rainfall of 1692.3 mm were recorded for this site (DHM 2017). Khadka et al (2018) found that the soil at the Simara site was moderately acidic in pH (5.67 ± 0.09), low in organic matter (0.74 ± 0.04%), and available Sulfur (0.8 ± 0.1 ppm). The sand, silt, and clay contents were 24.41 ± 0.59%, 54.57 ± 0.44%, and 21.03 ± 0.32%, respectively and categorized as silt loam and loam in texture.…”
Section: Study Sitesmentioning
confidence: 98%